Butyronitrile-based gel polymer electrolyte as well as preparation method and application thereof

The succinitrile-based gel polymer electrolyte prepared by using sodium difluoro(oxalic acid)borate, polyethylene glycol dimethacrylate and succinitrile, the problem of high electrolyte film thickness is solved, the combination of high ionic conductivity and film thickness is achieved, and the electrochemical performance of sodium ion batteries is improved.

CN119905651APending Publication Date: 2025-04-29BEIJING UNIV OF CHEM TECH

Patent Information

Application Number
CN202510041033.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing sodium ion battery electrolyte materials have the problem of high electrolyte film thickness, which cannot meet the needs of high ionic conductivity and thinner film thickness at the same time, resulting in poor electrochemical performance of the battery.

Method used

The electrolyte is prepared by mixing sodium difluoro(oxalic acid)borate, polyethylene glycol dimethacrylate and succinitrile, and infiltrated in the organic electrolyte to form a succinitrile-based gel polymer electrolyte with a film thickness of 25~50μm and has a higher ionic conductivity.

Benefits of technology

Achieve higher ionic conductivity and thinner electrolyte membranes, improving the electrochemical performance of the battery, including excellent sodium stability, long cycle stability and high temperature cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a succinonitrile-based gel polymer electrolyte as well as a preparation method and application thereof, belongs to the technical field of battery electrolytes, and solves the problem that a traditional solid electrolyte cannot meet the requirements of high ionic conductivity, high electrochemical window and high thermal stability at the same time. The preparation method comprises the following steps: mixing sodium difluoro (oxalate) borate, polyethylene glycol dimethacrylate and succinonitrile to obtain a mixture, and stirring the mixture at room temperature until a transparent polymerizable liquid is obtained; adding a photoinitiator into the obtained polymerizable liquid to form a transparent and uniform precursor; and infiltrating the precursor into a cellulose diaphragm, forming a solid polymer film through photopolymerization, then putting the solid polymer film into an organic electrolyte, and infiltrating to obtain the succinonitrile-based gel electrolyte. The gel-based electrolyte disclosed by the invention has the advantages of excellent thermal stability and relatively high conductivity, also has excellent sodium stability, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a succinonitrile-based gel polymer electrolyte, in particular to a succinonitrile-based gel polymer electrolyte and a preparation method and application thereof, belonging to the technical field of battery electrolytes. Background Art

[0002] Sodium-ion batteries have received widespread attention in recent years due to their cost advantages. However, the liquid organic electrolytes used in sodium-ion batteries have many disadvantages, such as poor chemical stability, flammability and leakage, which lead to major safety issues. The electrochemical window of ether electrolytes with good compatibility with sodium metal is often narrow, making it difficult to match high-voltage positive electrodes. Although ester electrolytes have a wider electrochemical window and can meet the needs of high-voltage positive electrodes, ester electrolytes have poor compatibility with sodium metal and serious side reactions at the interface, leading to rapid battery failure. Therefore, the safety and cycle stability of commercial traditional electrolytes seriously hinder the practical application of high-energy-density batteries.

[0003] At present, the new solid electrolyte can effectively avoid the leakage of electrolyte, thus solving the problem of poor safety performance of traditional liquid electrolyte. However, the solid electrolyte is a point-to-point interface contact mode, and its interface contact is poor compared to the traditional liquid electrolyte, resulting in a larger interface resistance value, and the corresponding ionic conductivity is very low, which makes it difficult for its solid electrolyte to be effectively used in the battery. For example, the Chinese patent with the authorization announcement number CN113956478B and the invention name of a polymer solid electrolyte and its preparation method and application discloses a preparation method of an electrolyte membrane comprising a polymer monomer, an alkali metal salt and succinonitrile, but its thickness is relatively high. In addition, the authorization announcement number CN11635074A and the invention name of a polymer sodium ion solid electrolyte and its preparation method and application discloses an application case of sodium difluorooxalate borate, but its ionic conductivity is relatively low, and the thickness of the electrolyte membrane is also relatively high.

[0004] Therefore, existing electrolyte materials currently have the problem of high electrolyte membrane thickness and cannot meet the requirements of high ionic conductivity and thinner film thickness at the same time. Summary of the invention

[0005] The purpose of the present invention is to solve the problems existing in the prior art, provide a succinonitrile-based gel polymer electrolyte and a preparation method and application thereof, prepare an electrolyte by mixing sodium difluoro(oxalato)borate, polyethylene glycol dimethacrylate and succinonitrile, and soak it in an organic electrolyte so that it has higher ion conductivity and thinner thickness, which is conducive to obtaining better electrochemical performance. In addition, the gel solid polymer electrolyte is applied to a sodium metal battery, which can promote uniform sodium deposition at the anode, effectively inhibit the growth of sodium dendrites and other problems, stabilize the sodium metal negative electrode, and have excellent stability to sodium.

[0006] To achieve the above object, the present invention adopts the following technical scheme: a method for preparing a succinonitrile-based gel polymer electrolyte, comprising the following steps: S1, mixing sodium difluoro(oxalato)borate, polyethylene glycol dimethacrylate, and succinonitrile to obtain a mixture, wherein the mass ratio of sodium difluoro(oxalato)borate to polyethylene glycol dimethacrylate is 1:2-5, and the mass ratio of polyethylene glycol dimethacrylate to succinonitrile is 1:1.2-2, and then stirring the mixture at room temperature for 1-2 hours until a transparent polymerizable liquid is obtained; S2, adding a photoinitiator to the polymerizable liquid obtained above, and then stirring at room temperature to form a transparent and uniform precursor; S3, infiltrating the precursor into a cellulose separator with a thickness of 25-50 μm, curing by photopolymerization, and obtaining a solid polymer electrolyte after drying; S4. Put the solid polymer electrolyte into the organic electrolyte for wetting, and finally obtain the succinonitrile-based gel electrolyte.

[0007] Furthermore, in step S2, the amount of the photoinitiator added is 0.5-1.25% of the mass of polyethylene glycol dimethacrylate, and the photoinitiator is 2,2-dimethoxy-2-phenylacetophenone (DMPA).

[0008] Furthermore, in step S3, the photopolymerization curing is performed under a 35W UV lamp for 3 to 10 minutes.

[0009] Furthermore, in step S3, the drying is carried out in a vacuum drying oven at 60° C. for 1 to 4 hours.

[0010] Furthermore, in step S4, the organic electrolyte is a mixture of NaClO4, EC, PC and FEC, wherein the volume ratio of EC to PC is 1:1, the content of NaClO4 in the mixed organic solvent of EC, PC is 1M, and the content of FEC is 5% of the mass of 1M NaClO4EC, PC, finally forming a 1M NaClO4EC, PC 5%FEC organic electrolyte.

[0011] The invention also discloses a succinonitrile-based gel polymer electrolyte prepared by the preparation method. The film thickness of the gel polymer electrolyte film is 25-50 μm; and the oxidation potential of the gel polymer electrolyte is 3.8-4.9V.

[0012] The invention also discloses application of the succinonitrile-based gel polymer electrolyte in a sodium ion battery.

[0013] The beneficial effects of the present invention are: 1) The present invention uses sodium difluorooxalatoborate with better film-forming performance to mix with polyethylene glycol dimethacrylate and succinonitrile to prepare the electrolyte, and infiltrates it in an organic electrolyte, which is beneficial to provide more stable cycle performance and ion conductivity, has higher ion conductivity and thinner thickness, and is beneficial to obtain better electrochemical performance; in addition, the gel solid polymer electrolyte is applied to sodium metal batteries, which can promote uniform sodium deposition at the anode, effectively inhibit the growth of sodium dendrites, stabilize the sodium metal negative electrode, have excellent stability to sodium, and have good application prospects.

[0014] 2) The succinonitrile-based solid electrolyte in the present invention is infiltrated with an organic electrolyte to be in a gel state, thereby obtaining a corresponding gel polymer electrolyte; the gel polymer electrolyte has excellent ability to inhibit the growth of sodium dendrites, excellent interface stability, high migration number, wide electrochemical window, excellent mechanical properties and thermal stability, and meets the requirements of high ionic conductivity and long cycle stability.

[0015] 3) The prepared gel-based electrolyte in the present invention is prepared into a lithium metal battery. The sodium metal battery based on the gel solid polymer electrolyte has excellent long-term cycle stability, high-temperature cycle stability and high-voltage cycle stability, as well as high coulombic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The EIS impedance diagrams of Examples 1 to 5 and Comparative Examples 1 to 4 measured in the present invention; Figure 2 It is a time-voltage diagram of a symmetrical battery assembled with the electrolyte of Example 2 measured in the present invention at room temperature; Figure 3 This is the LSV curve of the sodium battery assembled with the electrolyte of Example 2 measured in the present invention: Figure 4 This is a long cycle diagram of a button cell assembled with the electrolyte of Example 2 at room temperature measured in the present invention; Figure 5 This is a long cycle diagram of a button cell assembled with the electrolyte of Example 2 at 60° C. measured in the present invention; Figure 6 This is a long cycle diagram of a button cell assembled with the electrolyte of Example 2 at room temperature measured in the present invention; Figure 7 This is a long cycle diagram of the soft-pack battery assembled with the electrolyte of Example 2 measured in the present invention at room temperature. DETAILED DESCRIPTION

[0017] The present invention is further explained below in conjunction with the accompanying drawings and specific embodiments.

[0018] Embodiment 1: The present invention discloses a method for preparing a succinonitrile-based gel polymer electrolyte, comprising the following steps: S1. 0.1 g of sodium difluoro(oxalato)borate, 0.25 g of polyethylene glycol dimethacrylate and 0.3 g of succinonitrile were respectively mixed to form a mixed solution, and then the mixture was stirred at room temperature for 2 h until a transparent polymerizable liquid was obtained; S2, adding 0.0025 g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone (DMPA) to the polymerizable liquid obtained above, and then stirring at room temperature to form a transparent and uniform precursor; S3, infiltrating the precursor into a cellulose membrane with a thickness of 35 μm, UV photopolymerizing it under a 35 W UV lamp for 5 min, and then drying it in a vacuum drying oven at 60 ° C for 1 h to obtain a solid polymer electrolyte; S4. The solid polymer electrolyte is placed in an organic electrolyte solution of 1M NaClO4EC PC (V:V= 1:1) 5%FEC for wetting, and finally a succinonitrile-based gel electrolyte is obtained.

[0019] Performance test: The succinonitrile-based gel electrolyte prepared in Example 1 was placed between two stainless steel electrodes, and its ionic conductivity was tested using an electrochemical workstation. The test showed that the ionic conductivity of the succinonitrile-based gel electrolyte was 0.244 mS / cm at 25°C.

[0020] Embodiment 2: The present invention discloses a method for preparing a succinonitrile-based gel polymer electrolyte, comprising the following steps: S1. 0.1 g of sodium difluoro(oxalato)borate, 0.25 g of polyethylene glycol dimethacrylate and 0.45 g of succinonitrile were respectively mixed to form a mixed solution, and then the mixture was stirred at room temperature for 2 h until a transparent polymerizable liquid was obtained; S2, adding 0.0025 g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone (DMPA) to the polymerizable liquid obtained above, and then stirring at room temperature to form a transparent and uniform precursor; S3, infiltrating the precursor into a cellulose membrane with a thickness of 35 μm, UV photopolymerizing it under a 35 W UV lamp for 5 min, and then drying it in a vacuum drying oven at 60 ° C for 1 h to obtain a solid polymer electrolyte; S4. The solid polymer electrolyte is placed in an organic electrolyte solution of 1M NaClO4EC PC (V:V= 1:1) 5%FEC for wetting, and finally a succinonitrile-based gel electrolyte is obtained.

[0021] Performance test: The succinonitrile-based gel electrolyte prepared in Example 2 was placed between two stainless steel electrodes, and its ionic conductivity was tested using an electrochemical workstation. The test showed that the ionic conductivity of the succinonitrile-based gel electrolyte was 0.695 mS / cm at 25°C.

[0022] Embodiment 3: The present invention discloses a method for preparing a succinonitrile-based gel polymer electrolyte, comprising the following steps: S1. 0.1 g of sodium difluoro(oxalato)borate, 0.25 g of polyethylene glycol dimethacrylate and 0.5 g of succinonitrile were respectively mixed to form a mixed solution, and then the mixture was stirred at room temperature for 2 h until a transparent polymerizable liquid was obtained; S2, adding 0.0025 g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone (DMPA) to the polymerizable liquid obtained above, and then stirring at room temperature to form a transparent and uniform precursor; S3, infiltrating the precursor into a cellulose membrane with a thickness of 35 μm, UV photopolymerizing it under a 35 W UV lamp for 5 min, and then drying it in a vacuum drying oven at 60 ° C for 1 h to obtain a solid polymer electrolyte; S4. The solid polymer electrolyte is placed in an organic electrolyte solution of 1M NaClO4EC PC (V:V= 1:1) 5%FEC for wetting, and finally a succinonitrile-based gel electrolyte is obtained.

[0023] Performance test: The succinonitrile-based gel electrolyte prepared in Example 3 was placed between two stainless steel electrodes, and its ionic conductivity was tested using an electrochemical workstation. The test showed that the ionic conductivity of the succinonitrile-based gel electrolyte was 0.420 mS / cm at 25°C.

[0024] Embodiment 4: The present invention discloses a method for preparing a succinonitrile-based gel polymer electrolyte, comprising the following steps: S1. 0.1 g of sodium difluoro(oxalato)borate, 0.2 g of polyethylene glycol dimethacrylate and 0.40 g of succinonitrile were respectively mixed to form a mixed solution, and then the mixture was stirred at room temperature for 2 h until a transparent polymerizable liquid was obtained; S2, adding 0.0025 g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone (DMPA) to the polymerizable liquid obtained above, and then stirring at room temperature to form a transparent and uniform precursor; S3, infiltrating the precursor into a cellulose separator with a thickness of 25 μm, UV photopolymerizing it under a 35 W UV lamp for 5 min, and then drying it in a vacuum drying oven at 60 ° C for 1 h to obtain a solid polymer electrolyte; S4. The solid polymer electrolyte is placed in an organic electrolyte solution of 1M NaClO4EC PC (V:V= 1:1) 5%FEC for wetting, and finally a succinonitrile-based gel electrolyte is obtained.

[0025] Performance test: The succinonitrile-based gel electrolyte prepared in Example 4 was placed between two stainless steel electrodes, and its ionic conductivity was tested using an electrochemical workstation. The test showed that the ionic conductivity of the succinonitrile-based gel electrolyte was 0.587 mS / cm at 25°C.

[0026] Embodiment 5: The present invention discloses a method for preparing a succinonitrile-based gel polymer electrolyte, comprising the following steps: S1. 0.1 g of sodium difluoro(oxalato)borate, 0.5 g of polyethylene glycol dimethacrylate and 0.60 g of succinonitrile were respectively mixed to form a mixed solution, and then the mixture was stirred at room temperature for 2 h until a transparent polymerizable liquid was obtained; S2, adding 0.0025 g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone (DMPA) to the polymerizable liquid obtained above, and then stirring at room temperature to form a transparent and uniform precursor; S3, infiltrating the precursor into a cellulose separator with a thickness of 25 μm, UV photopolymerizing it under a 35 W UV lamp for 5 min, and then drying it in a vacuum drying oven at 60 ° C for 1 h to obtain a solid polymer electrolyte; S4. The solid polymer electrolyte is placed in an organic electrolyte solution of 1M NaClO4EC PC (V:V= 1:1) 5%FEC for wetting, and finally a succinonitrile-based gel electrolyte is obtained.

[0027] Performance test: The succinonitrile-based gel electrolyte prepared in Example 5 was placed between two stainless steel electrodes, and its ionic conductivity was tested using an electrochemical workstation. The test showed that the ionic conductivity of the succinonitrile-based gel electrolyte was 0.352 mS / cm at 25°C.

[0028] Comparative Example 1: A method for preparing a succinonitrile-based gel electrolyte, comprising the following steps: S1. 0.1 g of sodium difluoro(oxalato)borate, 0.25 g of polyethylene glycol dimethacrylate and 0.25 g of succinonitrile were respectively mixed to form a mixed solution, and then the mixture was stirred at room temperature for 2 h until a transparent polymerizable liquid was obtained; S2, adding 0.0025 g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone (DMPA) to the polymerizable liquid obtained above, and then stirring at room temperature to form a transparent and uniform precursor; S3, infiltrating the precursor into a cellulose separator with a thickness of 25 μm, UV photopolymerizing it under a 35 W UV lamp for 5 min, and then drying it in a vacuum drying oven at 60 ° C for 1 h to obtain a solid polymer electrolyte; S4. The solid polymer electrolyte is placed in an organic electrolyte solution of 1M NaClO4EC PC (V:V= 1:1) 5%FEC for wetting, and finally a succinonitrile-based gel electrolyte is obtained.

[0029] Performance test: The succinonitrile-based gel electrolyte prepared in Control Example 1 was placed between two stainless steel electrodes, and its ionic conductivity was tested using an electrochemical workstation. The test showed that the ionic conductivity of the succinonitrile-based gel electrolyte was 0.190 mS / cm at 25°C. This is because the lower content of succinonitrile compared to the present invention cannot completely dissociate the sodium salt, resulting in lower ionic conductivity.

[0030] Comparative Example 2: A method for preparing a succinonitrile-based gel electrolyte, comprising the following steps: S1. 0.1 g of sodium difluoro(oxalato)borate, 0.25 g of polyethylene glycol dimethacrylate and 0.6 g of succinonitrile were respectively mixed to form a mixed solution, and then the mixture was stirred at room temperature for 2 h until a polymerizable liquid was obtained; S2. 0.0025 g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone (DMPA) was added to the polymerizable liquid obtained above, and then stirred at room temperature. However, a uniform and transparent precursor could not be formed, and succinonitrile could not be completely dissolved. Therefore, photopolymerization and electrochemical performance testing could not be carried out.

[0031] Comparative Example 3: A method for preparing a succinonitrile-based gel electrolyte, comprising the following steps: S1. 0.1 g of sodium difluoro(oxalato)borate, 0.15 g of polyethylene glycol dimethacrylate and 0.45 g of succinonitrile were respectively mixed to form a mixed solution, and then the mixture was stirred at room temperature for 2 h until a polymerizable liquid was obtained; S2. 0.0025 g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone (DMPA) was added to the polymerizable liquid obtained above, and then stirred at room temperature. However, a uniform and transparent precursor could not be formed. The solubility of NaDFOB was limited, so photopolymerization and electrochemical performance testing could not be carried out.

[0032] Comparative Example 4: A method for preparing a succinonitrile-based gel electrolyte, comprising the following steps: S1. 0.1 g of sodium difluoro(oxalato)borate, 0.6 g of polyethylene glycol dimethacrylate and 0.45 g of succinonitrile were respectively mixed to form a mixed solution, and then the mixture was stirred at room temperature for 2 h until a transparent polymerizable liquid was obtained; S2, adding 0.0025 g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone (DMPA) to the polymerizable liquid obtained above, and then stirring at room temperature to form a transparent and uniform precursor; S3, infiltrating the precursor into a cellulose membrane with a thickness of 35 μm, UV photopolymerizing it under a 35 W UV lamp for 5 min, and then drying it in a vacuum drying oven at 60 ° C for 1 h to obtain a solid polymer electrolyte; S4. The solid polymer electrolyte is placed in an organic electrolyte solution of 1M NaClO4EC PC (V:V= 1:1) 5%FEC for wetting, and finally a succinonitrile-based gel electrolyte is obtained.

[0033] Performance test: The succinonitrile-based gel electrolyte prepared in Control Example 1 was placed between two stainless steel electrodes, and its ionic conductivity was tested using an electrochemical workstation. The test showed that the ionic conductivity of the succinonitrile-based gel electrolyte was 0.219 mS / cm at 25°C. This is because the higher polymer content compared with the present invention is not conducive to Na + transport, resulting in lower ionic conductivity.

[0034] like Figure 1 The EIS impedance diagrams of various embodiments and control examples are shown, and the ionic conductivity of each is calculated. In summary, the gel electrolyte membranes prepared in embodiments 1 to 5 all have a wide electrochemical window and a high ionic conductivity, and embodiment 2 is the best embodiment.

[0035] The gel electrolyte obtained in Example 2 was used to assemble a battery, and the following application tests were performed: like Figure 2 As shown in the figure, the time-voltage diagram of the symmetrical battery prepared in Example 2 at room temperature shows excellent sodium cycling stability at 0.1 mA cm -2 It can be cycled stably for 6000h at a current density of .

[0036] like Figure 3 As shown, a battery prepared by using metallic sodium as a reference electrode, a stainless steel sheet as a working electrode, and the succinonitrile-based gel electrolyte prepared in Example 2 as an electrolyte is used to test the electrochemical stability of the succinonitrile-based gel electrolyte by linear voltammetry (LSV), with a scanning range of 2.5V to 5.5V and a scanning speed of 0.1mV / s. It can be seen that the gel electrolyte has excellent electrochemical stability, and its stable voltage can reach 4.9V, which can meet the practical application under a high electrochemical window.

[0037] like Figure 4 As shown, the long cycle curve of the button cell assembled using the succinonitrile-based gel electrolyte of Example 2 as the electrolyte, sodium metal as the negative electrode, and sodium vanadium phosphate as the positive electrode material, at room temperature, with a current density of 1C and a voltage range of 2.5V-3.8V, was obtained by performing 2000 cycles of charge and discharge cycles. It can be seen that the succinonitrile-based gel electrolyte has an excellent long cycle surface, with a capacity retention rate of 85.6% after 2000 cycles and an average coulombic efficiency of 99.99%.

[0038] like Figure 5 As shown, the long cycle curve of the button battery assembled using the succinonitrile-based gel electrolyte of Example 2 as the electrolyte, sodium metal as the negative electrode, and sodium vanadium phosphate as the positive electrode material, was obtained by performing 1000 cycles of charge and discharge cycles at 60°C, with a current density of 1C and a voltage range of 2.5V-3.8V. It can be seen that the succinonitrile-based gel electrolyte has an excellent long cycle surface, with a capacity retention rate of 89.4% after 1000 cycles, an average coulombic efficiency of 99.38%, and excellent high temperature cycle stability.

[0039] like Figure 6 As shown, the long cycle curve of the button cell assembled using the succinonitrile-based gel electrolyte of Example 2 as the electrolyte, sodium metal as the negative electrode, and sodium vanadium fluorophosphate as the positive electrode material, was obtained by performing 1000 cycles of charge and discharge cycles at room temperature with a current density of 0.5C and a voltage range of 2.8V to 4.7V. It can be seen that the succinonitrile-based gel electrolyte has an excellent long cycle surface, with a capacity retention rate of 94.3 after 1000 cycles, an average coulombic efficiency of 99.71%, and excellent cycle stability under high voltage.

[0040] like Figure 7As shown, a soft-pack battery assembled using the succinonitrile-based gel electrolyte of Example 2 as the electrolyte, sodium metal as the negative electrode, and sodium vanadium phosphate as the positive electrode material is subjected to a long cycle curve at room temperature, with a current density of 0.2C and a voltage range of 2.5V-3.8V, and 200 cycles of charge and discharge cycles are performed. After 200 cycles, the capacity retention rate reaches 80.8%, and the average coulomb efficiency is 99.56%, which has certain practical application value.

[0041] The succinonitrile-based gel polymer electrolyte prepared in the embodiment of the present invention has a gel polymer electrolyte membrane with a thickness of 25 to 50 μm and an ion conductivity of 0.244 to 0.695 mS / cm.

[0042] The present invention adopts sodium difluorooxalatoborate with better film-forming performance to mix with polyethylene glycol dimethacrylate and succinonitrile to prepare the electrolyte, and infiltrates in an organic electrolyte, which is conducive to providing more stable cycle performance and ion conductivity, has higher ion conductivity and thinner thickness, and is conducive to obtaining better electrochemical performance; in addition, the gel solid polymer electrolyte is applied to the sodium metal battery, which can promote uniform sodium deposition at the anode, effectively inhibit the growth of sodium dendrites, stabilize the sodium metal negative electrode, have excellent stability to sodium, and have good application prospects.

[0043] The above description is only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in this field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a succinonitrile-based gel polymer electrolyte, characterized in that: The following steps are involved: S1, mixing sodium difluoro(oxalato)borate, polyethylene glycol dimethacrylate, and succinonitrile to obtain a mixture, wherein the mass ratio of sodium difluoro(oxalato)borate to polyethylene glycol dimethacrylate is 1:2-5, and the mass ratio of polyethylene glycol dimethacrylate to succinonitrile is 1:1.2-2, and then stirring the mixture at room temperature for 1-2 hours until a transparent polymerizable liquid is obtained; S2, adding a photoinitiator to the polymerizable liquid obtained above, and then stirring at room temperature to form a transparent and uniform precursor; S3, infiltrating the precursor into a cellulose separator with a thickness of 25-50 μm, curing by photopolymerization, and obtaining a solid polymer electrolyte after drying; S4. Put the solid polymer electrolyte into the organic electrolyte for wetting, and finally obtain the succinonitrile-based gel electrolyte.

2. The preparation method according to claim 1, characterized in that: In the step S2, the amount of the photoinitiator added is 0.5-1.25% of the mass of polyethylene glycol dimethacrylate, and the photoinitiator is 2,2-dimethoxy-2-phenylacetophenone (DMPA).

3. The preparation method according to claim 1, characterized in that: In the step S3, the photopolymerization curing is carried out under a 35W UV lamp for 2 to 15 minutes.

4. The preparation method according to claim 1, characterized in that: In step S3, the drying is carried out in a vacuum drying oven at 60° C. for 1 to 4 hours.

5. The preparation method according to claim 1, characterized in that: In step S4, the organic electrolyte is a mixture of NaClO4, EC, PC and FEC, wherein the volume ratio of EC to PC is 1:1, the content of NaClO4 in the mixed organic solvent of EC, PC is 1M, and the content of FEC is 5% of the mass of 1M NaClO4 EC, PC, finally forming a 1M NaClO4 EC, PC5%FEC organic electrolyte.

6. A succinonitrile-based gel polymer electrolyte prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The film thickness of the gel polymer electrolyte film is 25-50 μm; the oxidation potential of the gel polymer electrolyte is 3.8-4.9V.

7. Use of the succinonitrile-based gel polymer electrolyte according to claim 6 in a sodium ion battery.

Citation Information

Patent Citations

  • A polymer solid electrolyte, its preparation method and application

    CN113956478B

Cited By

  • Solvent-free transparent polymer electrolyte membrane and preparation method and application thereof

    CN120535789A